The effect of Zirconium Dioxide nanoparticles concentrations as filler on heat cured acrylic resin denture base toward viability of fibroblast cells (in vitro study) - Rudy S; Titik Ismiyati; Endang Wahyuningtyas (Majalah Kedokteran Gigi Indonesia, 2020)
Heat cured acrylic resin is the most commonly used denture base materials.  Zirconium dioxide (ZrO2) nanoparticles can be applied as additional filler to increase mechanical strength and to reduce the amount of residual monomer. The aim of this research is to analyze the effect of ZrO2 nanoparticles concentrations as filler on heat cured acrylic resin denture base toward viability of fibroblast cells. Twenty four disc-shaped heat cured acrylic resin plate (diameter 5 mm; width 2 mm), were divided into 4 groups (n=6), they were consisted of group I control (acrylic resin), group II acrylic resin with 2.5% ZrO2, group III acrylic resin with 5% ZrO2, and group IV acrylic resin with 7.5% ZrO2. Cell viability was obtained using MTT assay and ELISA plate reader. The result is examined with one way ANOVA followed by LSD post hoc assessment. The result showed highest cell viability percentage on experimental group of 2.5% ZrO2 with value as high as 97.49%. One way ANOVA test and LSD post hoc test showed a significant difference between groups (p<0.05). The conclusion of this research is ZrO2 nanoparticles concentration utilized as filler on heat cured acrylic resin denture base is effect to viability of fibroblast cells, and ZrO2 nanoparticles 2.5% shows the highest viability of fibroblast cell compared to 5% and 7.5% ZrO2 nanoparticles concentrations